Discovery and validation of plasma proteomic biomarkers relating to brain amyloid burden by SOMAscan assay - Shi, L; Westwood, S; Baird, A; Winchester, L; Dobricic, V; Kilpert, F; Hong, S; Franke, A; Hye, A; Ashton, N; Morgan, A; Bos, I; et al. (Elsevier, 2019)
Introduction: Plasma proteins have been widely studied as candidate biomarkers to predict brain amyloid deposition to increase recruitment efficiency in secondary prevention clinical trials for Alzheimer's disease. Most such biomarker studies are targeted to specific proteins or are biased toward high abundant proteins.